Blessing Precedes Cursing: Philosophical Reading of Genesis 3:16 - Chalier, Catherine (Religions, 2024)
Additional interpretations of Genesis 3:16 have often translated God’s words to the woman as a punishment, even a curse, brought upon the woman as the result of her disobedience. Moreover, this so-called curse of the woman has been read by many interpreters as final and irreversible, given that God himself had decreed it. Interestingly, however, no curse is uttered at all in this passage. Moreover, Genesis 3:16 is itself preceded by a divine blessing, given in Genesis 1 to the human couple. As a blessing, it constitutes a divine decree that can neither be overturned nor challenged. The purpose of this essay will be to go back to this divine blessing in Genesis 1, knowing that such a decree will be irrevocable no matter what the future holds for the human couple. This will in turn shed a revealing light on how we are to read and interpret Genesis 3:16. Not only do the words of God to the woman in Genesis 3:16 not constitute a curse, but Genesis 3:16 must be read against the backdrop of the blessing given in Genesis 1. This of course radically alters how this passage has hereto been interpreted as well as profoundly nuances its teaching on gender relations.